Evaluation of three photosynthetic species smaller than ten microns as possible standard test organisms of ultraviolet-based ballast water treatment. (September 2021) - Rivas-Zaballos, Ignacio; Romero-Martínez, Leonardo; Moreno-Garrido, Ignacio; Acevedo-Merino, Asunción; Nebot, Enrique
Abstract: The Ballast Water Management Convention (BWMC) establishes limits for viable organisms in discharged ballast water. However, organisms smaller than 10 μm are not considered in this regulation although they represent, in some regions, the majority of the phytoplankton organisms in marine water. The objective in this study is to assess three photosynthetic species smaller than 10 μm as potential standard test organism (STO) in experimentation focused on the inactivating efficacy of ultraviolet treatments (UV). A growth modelling method was employed to determine the reduction of the viable cell concentration under either light or dark post-treatment conditions to evaluate the importance of the photoreactivation. In spite of its moderate growth rate, the high UV resistance in combination with the abundance and worldwide distribution of Synechococcus sp. and the environmental importance of this species constitute important reasons for considering Synechococcus sp. as a valuable STO for ballast water treatment. Graphical abstract: Unlabelled Image Highlights: Organisms <10 μm should be considered in the Ballast Water Management Convention. Growth rate, UV resistance and darkness effects of the three species were analysed. Microorganism growth modelling is a suitable method to assess the effect of UV light. Synechococcus sp. seems a good test organism for UV-based ballast water treatment.